Genes that protect against the host-killing activity of the E3 protein of Bacillus subtilis bacteriophage SPO1. - Wei, P (1995)
A cloned rpoB gene, specifying an apparently mutant RNA polymerase beta subunit, protected Escherichia coli against the cytocidal effects of the E3 protein of bacteriophage SPO1, suggesting that RNA polymerase is the primary cellular target of the E3 protein. Two segments of the wild-type E. coli genome, one of which specifies a suppressor of dnaK mutations, and thus, possibly, a molecular chaperone, also provided protection when overexpressed, but wild-type rpoB did not.